VARIABILITY ANALYSIS OF SIGNIFICANT WAVE HEIGHTS AND WIND WAVES IN RIAU ARCHIPELAGO SEA PART ALKI 1 - Gandhi Napitupulu; Ayi Tarya; I Gede Merta Yoga Pratama; Ignatius Sonny Winardhie (Sam Ratulangi University, 2022)
The Riau Archipelago Sea is part of the Indonesian Archipelago Sea Lane (ALKI) 1, with a very high intensity of crossing ships. Analysis of surface wind speed and significant wave height is the most important for the safety and performance of offshore shipping. This research aims to study wave characteristics and wind speed by identifying the main factors that affect significant wave height and surface wind speed. Dominant factors that affect significant wave height and wind speed are needed to decide on the safest path and the best time before crossing in ALKI-1. Temporal and spatial analysis of the seasonal variability of significant wave height and wind speed using ECMWF data for 18 years. The data used are significant wave height data and wind speed every 6 hours during the period 2000 – 2018. Three observation points are used for temporal analysis, it is found that significant wave height and wind speed are influenced by two main factors, namely MJO and Monsoon. Maximum significant wave height and wind speed that occurs in the SON period for points 3 and the DJF period at points 1 and 2. MJO affects directly from phases one to eight for observation points 1, 2, and 3. The 4, 7, and 8 MJO phases affect the value of wave height and wave speed significantly, and the 1, 2, and 5 MJO phases affect wave height and wind speed weakly. Keywords: ALKI 1, MJO, MJO phase, Monsoon, Significant wave height, Wind speed.